Classroom Management and Students’ Science Learning at the Secondary Level in Public Schools - Lamsal, Uma Nath (Educational Journal, 2026)
The purpose of this study was to assess the status of classroom management practices by science teachers in community schools of Bhaktapur and examined its impact on learning science. The research used a convergent parallel mixed-methods design, which involved six science teachers from six government secondary schools, selected based on purposive sampling. To collect the data, Structured observation Checklist, Semi-structured interview guide line, Open-ended questionnaires and Field notes were used. The researchers used descriptive statistics to analyze quantitative data while thematic analysis served as the method for qualitative data analysis. The research found that 60% of classrooms lacking sufficient teaching materials and many laboratories were inadequately equipped. The teacher behavior assessment showed satisfactory results because teachers scored between 3.58 and 3.78 on the 5-point scale, but the knowledge-practice gap showed that teachers knew the effective strategies for instruction yet they did not apply these methods. Instructional management emerged as the weakest dimension, which showed below-average results in indicators that included classroom interaction (M = 2.84), disciplinary problem solving (M = 2.90), and encouraging shy students (M = 2.66). The students showed high interest (M = 4.00), but they only participated at moderate levels (M = 3.30). The integrated analysis established that poor classroom management practices together with physical resource shortages and contextual barriers from overcrowding and syllabus pressure create negative impacts on science learning outcomes. The study found that community secondary schools can enhance classroom management through three essential improvements, which involve physical resource investments and practice-oriented teacher professional development with continuous coaching and system-level reforms that include class-size reduction and curriculum realignment.